2014
DOI: 10.1186/1477-7525-12-101
|View full text |Cite
|
Sign up to set email alerts
|

Significant impairment of health-related quality of life in mainland Chinese patients with chronic hepatitis B: a cross-sectional survey with pair-matched healthy controls

Abstract: ObjectiveFew studies have evaluated health-related quality of life (HRQoL) of patients with chronic hepatitis B (CHB) in mainland China. We aimed at characterizing the impact of CHB on HRQoL in mainland Chinese and finding out factors associated with HRQoL.Methods460 CHB patients (323 with CHB only, 54 with compensated cirrhosis and 83 with decompensated cirrhosis) and 460 pair-matched healthy controls were recruited in Xi’an city. They answered a structured questionnaire including the Short Form 36 version 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 19 publications
3
24
0
3
Order By: Relevance
“…In studies conducted using different scales, it was determined that educational level [6], age [10], education period [11], annual income level [10], duration of the disease and receipt of antiviral therapy [10] affected HRQOL. In this study, HRQOL scores were found to be significantly lower in women, singles, and patients with other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted using different scales, it was determined that educational level [6], age [10], education period [11], annual income level [10], duration of the disease and receipt of antiviral therapy [10] affected HRQOL. In this study, HRQOL scores were found to be significantly lower in women, singles, and patients with other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some antiviral medications decrease HRQOL during the acute treatment period, the HRQOL of CHBV patients improves after completion of antiviral treatment [ 161 ]. In order to improve HRQOL of CHB patients, attention should be paid to the reduction of patients’ treatment cost burden and the provision of early health education accompanied with proper treatments [ 162 ]. A recent Chinese study evaluated the effect of comprehensive intervention on health-related quality of life and provided guidance on improving HRQOL for patients with CHB.…”
Section: Guidelinesmentioning
confidence: 99%
“…Previous studies identified a close association between hepatitis C, depression, and HRQoL [ 11 16 ]. Also, the association between HBV infection and quality of life was documented [ 17 21 ]. Despite increasing the interest in assessing HRQoL in different types of liver disease, research into other factors that can affect HRQoL in HBV + patients is lacking.…”
Section: Introductionmentioning
confidence: 99%